Chemotherapy With Erlotinib or Chemotherapy Alone in Advanced Non‐Small Cell Lung Cancer With Acquired Resistance to EGFR Tyrosine Kinase Inhibitors. (26th September 2013) - Goldberg, Sarah B.; Oxnard, Geoffrey R.; Digumarthy, Subba; Muzikansky, Alona; Jackman, David M.; Lennes, Inga T.; Sequist, Lecia V.
Abstract : Purpose: Epidermal growth factor receptor ( EGFR )‐mutant non‐small cell lung cancer has an oncogene‐addicted biology that confers sensitivity to EGFR tyrosine kinase inhibitors (TKIs). Published data suggest that EGFR addiction persists after development of TKI acquired resistance, leading many clinicians to continue TKI with subsequent chemotherapy; however, this strategy has not been formally evaluated. Methods: We retrospectively reviewed an institutional database to identify patients with advanced EGFR mutation with acquired resistance who subsequently received chemotherapy. Patients were classified as receiving chemotherapy with continued erlotinib or chemotherapy alone. We assessed differences in outcomes between the two strategies. Results: Seventy‐eight patients were included, 34 treated with chemotherapy and erlotinib and 44 treated with chemotherapy alone. Objective response rate was evaluable in 57 patients and was 41% for those treated with chemotherapy and erlotinib and 18% for those treated with chemotherapy alone. After adjusting for chemotherapy regimen and length of initial TKI course, the odds ratio for the response rate was 0.20 (95% confidence interval: 0.05–0.78; p = .02) favoring treatment with chemotherapy and erlotinib. The median progression‐free survival was 4.4 months on chemotherapy and erlotinib and 4.2 months on chemotherapy alone (adjusted hazard ratio = 0.79; 95% confidence interval: 0.48–1.29; p = .34). There was no difference in overall survival. Conclusion: This is the first study, to our knowledge, to demonstrate that continuation of EGFR TKI with chemotherapy in patients with acquired resistance improves outcomes compared with chemotherapy alone. We observed an improved response rate but no difference in progression‐free survival or overall survival. A larger prospective clinical trial is needed to evaluate this promising strategy further. Abstract : Published data suggest that epidermal growth factor receptor (EGFR) addiction persists after development of acquired resistance to an EGFR tyrosine kinase inhibitor (TKI), leading many clinicians to continue the TKI with subsequent chemotherapy; however, this strategy has not been formally evaluated. We retrospectively reviewed an institutional database and identified 78 patients with advanced EGFR ‐mutation with acquired resistance who subsequently received chemotherapy; 34 were treated with chemotherapy and erlotinib and 44 were treated with chemotherapy alone. This study demonstrates that continuation of EGFR TKI with chemotherapy in patients with acquired resistance improves outcomes compared with switching to chemotherapy alone. Abstract : 摘要 目的。 表皮生长因子受体 ( EGFR ) 突变型非小细胞肺癌存在致癌基因依赖性特点，这使得它对 EGFR 酪氨酸激酶抑制剂 (TKI) 具有很高的敏感性。已发表的数据表明，即使当癌灶产生 TKI 获得性耐药后，它仍旧对 EGFR 致癌基因存在依赖性，所以很多临床医生后续化疗时选择继续使用 TKI。但是，这一策略尚未得到正式评估。 方法。 通过对一个机构数据库进行回顾性评估，我们找出了那些在产生获得性耐药后又继续接受化疗的晚期 EGFR 突变型非小细胞肺癌患者。我们将这些患者分为两组：厄洛替尼联合化疗组和单纯化疗组。然后对两种策略的转归差异进行了评估。 结果。 本研究共纳入了 78 名患者，其中 34 名接受了厄洛替尼联合化疗，44 名接受了单纯化疗。有 57 名患者可进行客观见效率评价。结果显示，厄洛替尼联合化疗组的客观见效率为 41%，而单纯化疗组的客观见效率为 18%。经校正化疗方案及初始 TKI 疗程后，两组的见效率比值比为 0.20（95% 置信区间：0.05‐0.78； p = 0.02），表明厄洛替尼联合化疗的效果优于单纯化疗。厄洛替尼联合化疗组的中位无进展生存期为 4.4 个月，而单纯化疗组则为 4.2 个月（校正后风险比 = 0.79；95% 置信区间：0.48 –1.29； p = 0.34）。总体生存期并无显著差异。 结论。 据我们所知，本研究是第一次证实，对已产生获得性耐药的患者继续进行 EGFR TKI 联合化疗与进行单纯化疗相比更有助于改善患者的预后。我们观察到，患者的见效率有所改善，但无进展生存期或总体生存期并无显著差异。我们需要通过更大规模的前瞻性临床试验来进一步评估这一充满希望的治疗策略。 The Oncologist 2013;18:1214–1220